Platelet-Rich Plasma Injection Modulates Inflammatory Cytokines in Temporomandibular Joint Disorders: A Cross-Sectional Study - Karar Abdulzahra Mahdi; Muhassad H. Al-Mudhafar; Dunya Malhan Hanweet (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Temporomandibular disorders are conditions that affect the structures of the jaw joint. These conditions can cause a variety of symptoms, including discomfort, restricted movement, and the inability to perform certain functions. Objectives: To investigate the impact of providing platelet-rich plasma (PRP) injections on the levels of interleukin 8 (IL-8) and tumor necrosis factor-alpha (TNF-α) in the synovial fluid of patients who were experiencing traumatic knee dislocations (TMDs), the objective of this study was to investigate the impact of these injections. Methodology: Intra-articular PRP injections were administered to 33 individuals diagnosed with TMDs. Samples of synovial fluid were taken both at baseline and two months after the PRP injection. The determination of TNF-α and IL-8 concentrations was carried out by utilizing ELISA Kits. For statistical analysis, the paired t-test was utilized. Results: TNF-α levels (baseline mean = 26.55 pg/mL, post-PRP, mean = 18.79 pg/mL) and IL-8 levels (baseline mean = 72.28 pg/mL, post-PRP mean = 6.83 pg/mL) were significantly reduced after PRP therapy. Conclusion: The decrease in TNF-α and IL-8 levels following PRP injection indicates a potential anti-inflammatory effect in TMDs. PRP’s growth factors may help reverse degenerative changes by promoting tissue regeneration and repair.